A new approach to meteorological observations on remote polar glaciers using open-source internet of things technologies - Filhol, Simon; Lefeuvre, Pierre-Marie; Ibañez, Juan David; Hulth, John; Hudson, Stephen R.; Gallet, Jean-Charles; Schuler, Thomas Vikhamar; Burkhart, John F. (Frontiers in Environmental Science, 2023)
Key regions of the world lack sufficient infrastructure to collect geophysical observations, often due to logistical challenges such as difficult accessibility and cost. With the advent of Internet-of-Things (IoT) technologies and low-cost electronics, it is possible today to build monitoring systems collecting spatially distributed, in-situ data with real-time connectivity to online servers for immediate and long-term usage at costs comparable to those of a single autonomous weather station. We present here a custom-built, modular system that collects quality data, and, that is, robust to adverse meteorological conditions and lack of energy. It integrates commercial and custom-built sensors connected to a node (main device) that manages power, data and radio communication. Data is sent to gateways and then to a server that parses, stores and quality controls the data. We deployed two networks in the vicinity of Ny-Ålesund in Svalbard, and operated from May 2021 to April 2022 to measure meteorological and glaciological variables. Our system collected reliable data and had sufficient power resources to survive 4–5 months of darkness during the polar night. Here, we present the design considerations and performance metrics, report our lessons learned from this challenging deployment, and suggest pathways for future improvements.